Unbundling the incumbent: Evidence from UK broadband - Valletti,T; Nardotto,M; Verboven,F (Journal of the European Economic Association, 2015)
We consider the impact of a regulatory process forcing an incumbent telecom operator to make its local broadband network available to other companies (local loop unbundling, or LLU). Entrants are then able to upgrade their individual lines and offer Internet services directly to customers. Employing a very detailed data set covering the whole of the United Kingdom, we find that, over the course of time, many entrants have begun to take advantage of unbundling. LLU entry only had a positive effect on broadband penetration in the early years, and no longer in the recent years as the market reached maturity. In contrast, LLU entry continues to have a positive impact on the quality of the service provided, as entrants differentiate their products upwards compared to the incumbent. We also assess the impact of competition from an alternative form of technology (cable) which is not subject to regulation, and what we discover is that inter-platform competition has a positive impact on both penetration and quality.